Adapting to climate change: the case of snow-based tourism in Afriski, Lesotho. Issue 1 (2nd January 2021) - Hoogendoorn, Gijsbert; Stockigt, Lara; Saarinen, Jarkko; Fitchett, Jennifer M.
ABSTRACT: Climate change poses significant challenges to the tourism sector, with snow-based tourism particularly threatened. Snow-based tourism is largely dependent on adaptation, including snowmaking practices and product diversification. In the global south, the limited snow-based tourism products face similar challenges to the global north, but with significantly higher vulnerability and lower adaptive capacity. By making use of a questionnaire survey and personal in-depth interviews this paper examines adaptation mechanisms and the perceptions held by tourists and managers at Afriski, Lesotho. While Afriski already implements adaptive mechanisms, considering the current global environmental change projections for southern Africa, greater adaptive action is necessary.